An ISA-95-based production scheduling system for high-mix,low-volume manufacturing - Phua, Tiong Lee. (2010)
Globalization is changing the way companies do business. Goods are getting cheaper and cheaper with the lowering down of trade barriers between countries. The challenges that companies faced will be system to meet ever changing off threat from rival. This has cause companies to look more closely into how to integrate their manufacturing system with that of their enterprise systems. In the 1990s, manufacturing org with high cost and low probability of succes standard used in their various system like enterprise resource supply chain. This has become a challenge for organization same standard. Since then there is a demand for a generic and simple standard to apply across all applications in an enterprise systems. Responding to the pressure to companies turn to the use of This project performs an in application for the Production Planning and Scheduling domain applications are designed with the same standard and different systems. In addition the author has created an interface to allow developer and end users to make use of it to make their own system ISA has made it simple and easy for users to understand and implement ISA FYP: An ISA-95-Based Production Scheduling System for High-Mix, Low Abstract to find methods to lower manufacturing cost market demand so as to remain competitive and to . anufacturing organizations attempt to integrate their systems are success due to the involvement of different planning, scheduling and to base their ISA-95 standard to integrate their systems. in-depth investigation of the ISA-95 standar ed make it easy to be integrated into ISA-95 compliance. This interface mple Low-Volume Manufacturing iii and a flexible fend ir faced integration on a cut cost, standard and its so that every ISA-95 standards.